Innate Lymphoid Cells in Intestinal Inflammation - Geremia, Alessandra; Arancibia-Cárcamo, Carolina V. (Frontiers in Immunology, 2017)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder of the intestine that encompasses Crohn’s disease (CD) and Ulcerative Colitis. The cause of IBD is unknown, but the evidence suggests that an aberrant immune response towards the commensal bacterial flora is responsible for disease in genetically susceptible individuals. Results from animal models of colitis and human studies indicate a role for innate lymphoid cells (ILC) in the pathogenesis of chronic intestinal inflammation in IBD. ILC are a population of lymphocytes that are enriched at mucosal sites, where they play a protective role against pathogens including extracellular bacteria, helminthes and viruses. ILC lack an antigen-specific receptor, but can respond to environmental stress signals contributing to the rapid orchestration of an early immune response. Several subsets of ILC reflecting functional characteristics of T helper subsets have been described. ILC1 express the transcription factor T-bet and are characterized by secretion of IFNγ, ILC2 are GATA3+ and secrete IL5 and IL13 and ILC3 depend on expression of RORγt and secrete IL17 and IL22. However, ILC retain a degree of plasticity depending on exposure to cytokines and environmental factors. IL23 responsive ILC have been implicated in the pathogenesis of colitis in several innate murine models through the production of IL17, IFNγ and GM-CSF. We have previously identified IL23 responsive ILC in the human intestine and found they accumulate in the inflamed colon and small bowel of patients with CD. Other studies have confirmed accumulation of ILC in CD with increased frequencies of IFNγ secreting ILC1 in both the intestinal lamina propria and the epithelium. Moreover, IL23-driven IL22 producing ILC have been shown to drive bacteria-induced colitis-associated cancer in mice. Interestingly, our data show increased ILC accumulation in patients with IBD and primary sclerosing cholangitis, who carry an increased risk of developing colorectal cancer. ILC may play an important amplifying role in IBD and IBD-associated cancer, through secretion of inflammatory cytokines and interaction with other immune and non-immune cells. Here, we will review the evidence indicating a role for ILC in the pathogenesis of chronic intestinal inflammation.